Effect of the Crosslinking Between the Asphalt and Polyethylene on the Viscoelastic Properties of Polyethylene Melt Extruding Through Capillary - Mostafa M. Naeem; Moayad N. Khalaf; Hashmya Abd-Alkarem; Mazen Abd-Alhasan (University of Thi-Qar Journal of Science, 2019)
The viscoelastic properties of polyethylene were studied with different percent of asphalt(1%,3%,5%,7% and 10% ) and 1% of organic peroxide as crosslinking agent. The data shows thatthe 1% of asphalt loading in the polymer decrease the shear stress and viscosity of the matrixpolymer in all the test temperature (170,190,210 and 230oC) .The best percent of asphalt that givescontrolled crosslinking between the polymer chains was 1% asphalt loading, while higher asphaltpercent will increase the chain entanglements .